Comparative analysis of electrochemical energy storage technologies for smart grid - Surender Reddy Salkuti (Universitas Ahmad Dahlan, 2020)
This paper presents a comparative analysis of different forms of electrochemical energy storage technologies for use in the smart grid. This paper addresses various energy storage techniques that are used in the renewable energy sources connected to the smart grid. Energy storage technologies will most likely improve the penetrations of renewable energy on the electricity network. Consequently, energy storage systems could be the key to finally replacing the need for fossil fuel with renewable energy. It is hard to evaluate the different types of energy storage techniques between themselves due to the fact that each technology could be used in a different way and are more like compliments. Subsequently, for the purposes of this paper, it is seen that the use of energy storage technologies will increase the supply, and balances out the demand for energy.